Presidents' Day - Alden, Laura, 1955-; Friedman, Joy (Chicago : Children's Press, 1994)
Carey's class learns many interesting things about presidents Washington and Lincoln and celebrates both birthdays on Presidents' Day. Includes an activities section.
2.5
K-3
Keywords: Lincoln, Abraham, -- 1809-1865 -- Fiction; Washington, George, -- 1732-1799 -- Fiction; Lincoln, Abraham, -- 1809-1865 -- Fiction; Washington, George, -- 1732-1799 -- Fiction; Presidents' Day -- Juvenile fiction; Presidents' Day -- Fiction; Presidents' Day -- Fiction